Studies on the interaction of FKBP65, a putative molecular chaperone, with tropoelastin and an elastin model polypeptide - Cheung, Kevin (My University, 2006)
FKBP65 is a 65 kDa FK-506 binding protein containing 4 putative peptidyl prolyl isomerase (PPiase) domains, whose expression level parallels that oftropoelastin, the soluble precursor ofelastin. Studies from other laboratories have established that FKBP65 associates with tropoelastin (TE) in the endoplasmic reticulum (ER) and dissociates from TE before reaching the Golgi apparatus (Patterson et al., 2000). TE contains 12% proline residues, which are often found in VPGVG repeats, and it has been suggested that these repeats formp-turns and subsequently P-spirals (Urry et al., 1992). The formation ofthe P-spiral is thought to be essential to endow the elastic properties of the elastin fibers. In order to form a P-turn, the proline residue at position 2 ofthe VPGVG sequence must be in trans conformation (Urry et al., 1995). Therefore, it was hypothesized by Davis and coworkers (Davis et al., 1998) that FKBP65, as a PPiase, may play an important role in the folding oftropoelastin by enhancing the formation ofP-turns in the ER, and thus elastic fiber formation. In the present study we have studied the coacervation (a reversible, temperature-dependent, self association process) ofTE and recombinant elastin model polypeptide, EP4, in the absence or presence ofrecombinant FKBP65 (rFKBP65). rFKBP65 was shown to enhance the coacervation process of TE, by lowering the coacervation temperature (T c) and increasing the overall extent of coacervation. In the kinetic study ofcoacervation ofTE at a constant temperature, rFKBP65 increased both the initial rate ofthe coacervation process and the overall extent ofcoacervation. These effects are specific to rFKBP65, as FKBP12 has no effect on the coacervation process. Rapamycin, an inhibitor ofthe PPiase activity ofFK-506 binding proteins, did not alter rFKBP65's effect on TE coacervation.
In contrast to TE, rFKBP65 affected the coacervation process ofEP4 by increasing the T c, and by enhancing the dissociation of coacervates when temperature is decreased. Once again, these effects are specific to rFKBP65, as FKBP12 and BSA were shown to have no effect on the coacervation ofEP4. The effect of small pH changes on rFKBP65 was also investigated, and it was found that lowering the pH from 7.5 to 6.0 had no effect on rFKBP65's secondary structure or coacervation-altering activity.
In summary, this study, along with an earlier study from this laboratory, has shown that FKBP65 affects the coacervation process ofTE. In addition, the coacervation pro·cess of an elastin model polypeptide, EP4, is also modulated by FKBP65. However, the mechanism ofthese effects remains unclear. Nevertheless, along with the data established by other laboratories, FKBP65 does appear to be a strong candidate as a molecular chaperone for tropoelastin, and may play an important role in the elastogenesis process.
Keywords: FKBP65; molecular chaperone; putative; tropoelastin; elastin model; polypeptide